Efficacy of food preservatives and volatile compounds in the control of ochratoxin a production by penicillium species - Vankudoth, Koteswara Rao; Rao, K. Narasimha; Sivadevuni, Girisham; Reddy, S. M. (Proceedings of the National Academy of Sciences, India - Section B: Biological Sciences, 2015)
In the present investigation different volatile compounds and food preservatives were tested for their efficiency in the control of growth and ochratoxin A (OTA) production by Penicillium verrucosum and Penicillium nordicum. Volatiles such as phenols and formic acid which have no residual effect were proved to be effective in checking the growth and OTA production by both the species of Penicillium under study. Vapours of phenols and formic acid significantly inhibited OTA produced by P. verrucosum, while aniline and toluene inhibited the OTA production by P. nordicum to a significant level. A positive correlation coefficient was observed between the growth and toxin production by P. verrucosum (0.55) and P. nordicum (0.66) against different volatile compounds tried. Among food preservatives, sodium acetate and sodium metabisulphate were responsible for total inhibition of OTA production by P. verrucosum at 150 lg/ml concentration. P. nordicum proved to be comparatively more resistant to these substances than P. verrucosum. In conclusion of present investigation, phenol, formic acid, amyl alcohol, propionic acid, sodium acetate and sodium metabisulphate were found to be effective in checking the growth and OTA production by both the species of Penicillium under investigation, and can be exploited in protecting the poultry feed from unwanted mould growth and mycotoxin production.

Influence of carbon and nitrogen source on growth, DON and NIV production by two species of fusarium isolated from finger millets - Penugonda, Shilpa; Rao, Vankudoth Koteswara; Rao, K. Narasimha; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Influence of different carbon [C] and nitrogen [N] source on the growth and Deoxynivalenol [DON] and Nivalenol [NIV] production by Fusarium aethiopicum and Fusarium culmorum was investigated. Methods: Seven days old monosporic cultures of F. aethiopicum strain GSKUMB [KJ21085] and F. culmorum strain GSKUMB [KJ190159] were grown in CYA broth and incubated at 27±2°C on the rotary shaker at 120 rpm for 21 days. At the end of incubation period, cultures were harvested for determination of fungal growth (biomass). The resultant culture filtrates were extracted twice with ethyl acetate and concentrated. One ml of final concentrate in methanol was employed for detection of DON and NIV with the help of RP-HPLC. Results: The highest amount of DON and NIV were produced by F. aethiopicum in the presence of D-mannose and D-galactose as C source, while the highest amount of biomass was recorded on maltose and succinic acid. F. culmorum produced maximum amount of toxins in the presence of D-glucose, D-mannitol and D-fructose. Sodium nitrate was most favorable nitrogen source as it induced maximum amount of toxins by F. aethiopicum, while L-methionine, L-asparatic acid and L-tryptophan were next preferred N source. In contrast, highest biomass of fungus was obtained with L-lysine, L-glutamine and L-tyrosine. F. culmorum produced maximum amount of toxin and biomass with potassium nitrate and L-tyrosine respectively. Conclusion: Present species of Fusarium differed varied both in toxins (DON, and NIV) and biomass production. Their response of fungi under investigation towards C and N sources is also varied.